Pre-harvest cinnamic acid and potassium cinnamate improve postharvest quality and storability of ‘Kyoho’ grapes - Hu, Yulong; Wang, Chaoxia; Tian, Shufen; Wang, Rong; Ma, Chuang; Jiang, Jianfu (Frontiers in Plant Science, 2026)
Frequent high temperatures render ‘Kyoho’ grapes prone to postharvest softening, berry drop, and insufficient coloration. To address these challenges, this study investigated the effects of preharvest foliar sprays of cinnamic acid (CA) and potassium cinnamate (PC) on fruit quality and storability. Grapes were treated with different concentrations of CA or PC from veraison to maturity, and followed by evaluation after 96 hours of storage at 25°C. The results indicated that high concentrations of CA and PC significantly enhanced fruit quality by increasing total soluble solids (TSS) content and the accumulation of antioxidants (e.g., total phenols, flavonoids, and ascorbic acid), while reducing titratable acidity (TA) and improving texture properties including peel puncture strength, flesh firmness, and elasticity. Furthermore, these treatments inhibited hydrolase activity (e.g., cellulase and pectinase), decreased berry drop and decay incidence, and suppressed pathogen growth (especially Penicillium and Aspergillus). Notably, 10 mmol·L-1 CA was most effective in maintaining TSS and antioxidant reserves, whereas 10 mmol·L-1 PC excelled in preserving fruit firmness, improving pedicel stability, and extending storage life. These beneficial effects were mediated by regulating the activity of key enzymes (e.g., SOD, POD, PPO, C4H, and 4CL) and the expression of relevant genes (e.g., VvPAL, VvCHS, and VvANS), thereby providing a practical technical foundation for the postharvest preservation of ‘Kyoho’ grapes.